Design and control of variable length hyper redundant robot - Jamali, Annisa; Khan, Md. Raisuddin; Rahman, Md. Mozasser (Elsevier, 2012)
This paper puts forward a design concept of Variable length Hyper-redundant robot, consisting of eight links and their encloser system. Each of the rigid links is connected via actuated revolute joints in a chain. The robot will operate on the principle that one by one link will be coming out of the housing and moving towards the desired position. The robot can be a practical and cost saving approach in complex and unstructured area. In one particular operation, the variable length Hyper-redundant robot can provide shorter trail and shorter time as well compared to fixed number of links. The basic robotics analyses, dynamics simulation and experiment are also shown. The prototype developed is used as a proof of the concept.